Effectiveness of NaCl Solution in Cement with Different Concentrations Fertilization and Hatching Rate of Striped Catfish Eggs (Pangasianodon hypophthalmus) - Dina, Indah Ayu A’inin; Aryani, Netti; Nuraini, Nuraini (Jurnal Akuakultur SEBATIN, 2024)
The research was conducted in January - February 2022, at the Hatchery and Fish Breeding Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This study aims to determine the effectiveness of NaCl solution in cement with different concentrations on the value of fertilization and hatching of catfish eggs (Pangasianodon hypopthalmus). The experiment used a one-factor Completely Randomized Design (CRD) method with 4 treatment levels and 3 replications, namely: P1: addition of 0.9% physiological NaCl solution, P2: 0.3% NaCl solution, P3: 0.5% NaCl solution, and P4: 0.7% NaCl solution. The results showed that the use of doses of NaCl solution with different concentrations affected the motility value of spermatozoa, the degree of fertilization, the hatching of eggs and dilution. The dose treatment with a concentration of 0.5% produced the highest spermatozoa motility value, which is very good (++++) with characteristics like: big and numerous waves, dark, thick, and actively moving quickly, fertilization rate of 84.32%, hatching rate of 85.39%, and survival rate of 84.23%. The water quality parameters were 29 - 30oC, pH 6.2 - 7 and dissolved oxygen 6.5 - 7.2 mg/L